6-2z=-4

Simple and best practice solution for 6-2z=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-2z=-4 equation:


Simplifying
6 + -2z = -4

Solving
6 + -2z = -4

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -2z = -4 + -6

Combine like terms: 6 + -6 = 0
0 + -2z = -4 + -6
-2z = -4 + -6

Combine like terms: -4 + -6 = -10
-2z = -10

Divide each side by '-2'.
z = 5

Simplifying
z = 5

See similar equations:

| 1-(2/t)-(35/t^2)=0 | | Ln=1.6873 | | -200x*2x= | | 2x+5=+15+4 | | e=1/6πv^2r | | q=a((5.3)) | | 6x=y^2-6y+39 | | (X)48=-18 | | 9p-22=-31+8p | | 24-(15x-1)= | | -7(15+h)=56 | | 2(-3x+4)-x=1x | | b/r-t/r=1 | | 4x-2y+8x=10y | | 8(3c-9)= | | ((3v^4y^5)/(15vw^2-9v^4)) | | 2.5=-0.2x(x-13.5) | | 5(p+8)= | | -0.2x^2+2.7x-2.5=0 | | x+y=3y-10 | | z^6+iz^3+i-1=0 | | 150=50x | | 195=39x | | 5(x)+5(x+3)=225 | | 3(2x+x)=2700 | | 5a-5+2a-7= | | 2x+x*3=2700 | | x^06=0.75 | | 10*x+6*(0.8-t)=6 | | 2x^2-5x+28=0 | | 6lny=3lne^2-9lnx | | x+y+6+5x+2y=180 |

Equations solver categories